2022
DOI: 10.1128/aem.00835-22
|View full text |Cite
|
Sign up to set email alerts
|

The α- and β-Subunit Boundary at the Stem of the Mushroom-Like α 3 β 3 -Type Oxygenase Component of Rieske Non-Heme Iron Oxygenases Is the Rieske-Type Ferredoxin-Binding Site

Abstract: We clarified the critical amino acid residues of the oxygenase component (Oxy) of Rieske non-heme iron oxygenase (RO) for binding with Rieske-type ferredoxin (Fd). Our results showed that Rieske-type Fd-binding site is commonly located at the stem (side-wise site) of the mushroom-like α 3 β 3 quaternary structure in many ROs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 57 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…Sequence alignment with other ROs indicate that these two positive charged residues presumably play an essential role in the side-wise protein interaction between RO-Fds and heterohexameric RO-Oxys (α 3 β 3 ). [135] Unlike described charge-transfer complexes in three-component ROs, considerably less structural information on the interaction between RO-Reds and their associated RO-Oxys is reported. To the best of our knowledge, the only example in the literature described is the complex between NdmA and the Fd-domain of the associated RO-Red NdmD (NdmD Fd , PDB: 6ICM).…”
Section: Redox Partner Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence alignment with other ROs indicate that these two positive charged residues presumably play an essential role in the side-wise protein interaction between RO-Fds and heterohexameric RO-Oxys (α 3 β 3 ). [135] Unlike described charge-transfer complexes in three-component ROs, considerably less structural information on the interaction between RO-Reds and their associated RO-Oxys is reported. To the best of our knowledge, the only example in the literature described is the complex between NdmA and the Fd-domain of the associated RO-Red NdmD (NdmD Fd , PDB: 6ICM).…”
Section: Redox Partner Interactionsmentioning
confidence: 99%
“…[24,134] Recently, specific residues at the surfaces of the heterohexameric RO-Oxy (α 3 β 3 ) and associated RO-Fd of CDO from P. fluorescens IP01 have been determined as crucial for electron transfer between the corresponding Rieske [2Fe-2S] clusters. [135] Thereby, docking studies in combination with alanine scanning revealed two residues crucial for RO-Oxy reduction. As reported, no reduction of the [2Fe-2S] cluster within the Rieske domain of RO-Oxy was observed when exchanging Lys117 in the αsubunit and Arg65 in the β-subunit.…”
Section: Redox Partner Interactionsmentioning
confidence: 99%
“…The β subunits of the α 3 β 3 enzymes sit more than 10 Å away from the active site. Residues implicated in binding the reductase are shown in an oval and highlighted in purple [ 49 ]. (b) The α 3 α 3 architecture of PDO reveals that the trimers are staggered and likely stabilized by additional secondary structures found in each α subunit (dark blue and orange).…”
Section: Figurementioning
confidence: 99%
“…Other reports suggest that the β subunits could be involved in dictating the substrate scopes and preferences of different Rieske oxygenases [ 46 – 48 ]. Most recently, residues from both the α and β subunits were reported to mediate interactions with the ferredoxin component of a dedicated partner reductase system [ 49 ]. Mapping of these residues onto naphthalene dioxygenase (NDO) reveals that the reductase, as observed in the α 3 enzymes, also sits at the subunit–subunit interfaces ( Figure 2a , d ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation